Neurocysticercosis in Pregnancy - Kaur, Amandeep; Kaur, Balwinder; Mohi, Manjit Kaur (New Frontiers in Medicine and Medical Research Vol. 13, 2021)
First episode of Seizure in a pregnant woman is always presumed as Eclampsia. Diagnosis of neurocysticercosis in pregnancy is often confounded by fact that associated symptoms of headache, nausea & vomiting, visual disturbance, neurological changes and seizures maybe presentation of Eclampsia Syndrome. Neurocysticercosis, although rare, is an important cause of first-time convulsions in pregnancy specially in tropical country like India. It can be very well treated with minimal interruption to the course of the pregnancy as in non-pregnant women and medical treatment is effective in most cases. In this this chapter along with management, we also report cases of pregnant patients with atypical features which were misdiagnosed as Eclampsia but they were later diagnosed to be Neurocysticercosis on Neuroimaging.